Making sense of invulnerability at work—a qualitative study of police drive - Dorn, Lisa; Brown, Brian J. (Elsevier, 2003)
This paper reports a qualitative study of 54 police drivers who were interviewed about their views on police driver training, driving strategies and their accident involvement. Study of the transcribed interviews indicated that officers constructed narratives of themselves as being highly aware of hazards presented by other road users and they used a variety of discursive devices to minimise their own culpability and attribute risk elsewhere. Rather than maintaining a straightforward ‘illusion of invulnerability’ they were formulating a ‘topography of risk’ in which they were responding to hazards presented by suspects or other road users. Their meticulously detailed accounts of the circumstances surrounding accidents serve to place them as knowledgeable and impartial participants and create a sense of expertise and authority. Training initiatives could profitably seek to challenge this ‘topography of risk’ and sense of authority so that drivers more fully appreciate the hazard they may present to themselves and
Keywords: Risk; Hazard perception; Driving behaviour; Police